Takhrij and Syarah Hadith of Chemistry: Prohibition of using Gold for Men - Friska Liesanty Setiawan; Alfi Salwa Qibty; Solehudin Solehudin; Ecep Ismail; Adi Mulyana Supriatna (Gunung Djati Conference Series, 2021)
The purpose of this research is to discuss the hadith of the Prophet about the prohibition of using gold for men. This research method is qualitative through the takhrij and sharah hadith approaches with chemical analysis. The results and discussion of this study is the prohibition of using gold for men. The conclusion of this research is takhrij and syarah hadith of the Prophet. prohibits the use of gold for men